LPIC-2 Linux Engineer (202-450) - Pezet, Don; Goodwin, Sophie (Packt Publishing, 2024)
The course begins by laying a solid foundation with the installation and configuration of the BIND DNS server, moving on to the intricacies of creating forward and reverse lookup zones, which are pivotal for network navigation and management. It emphasizes the critical role DNS plays in network infrastructure, detailing troubleshooting techniques and ways to enhance mail server support through DNS configurations. It continues with securing BIND using DNSSEC, ensuring data integrity and authentication across the network. The course focuses on web server deployment and management, starting with Apache, which includes virtual server configuration, SSL encryption, and URL redirection, before transitioning to the Squid proxy server setup, user authentication, and access restrictions. It also covers Nginx for web serving and reverse proxy applications, highlighting its flexibility and efficiency. The course wraps up with an exploration of network file sharing and server management using Samba and NFS, DHCP server configuration, OpenLDAP for authentication, Postfix for SMTP services, and secure communications with OpenVPN and SSH. Additionally, it touches on firewall management with iptables, FTP server setup, and the importance of Fail2ban for security.
Online resource; title from title details screen (O'Reilly, viewed March 19, 2024)
Keywords: Linux -- Study guides -- Examinations; Operating systems (Computers) -- Study guides -- Examinations; Computer networks -- Study guides -- Examinations; Electronic data processing personnel -- Certification; Systèmes d'exploitation (Ordinateurs); Examens; Guides de l'étudiant; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet